Local Community Participation in the Implementation of REDD+: The Case of Meru Betiri National Park - Dirgantara, Pradipta (Universitas Muhammadiyah Yogyakarta, 2020)
Reducing Emissions from Deforestation and Forest Degradation Plus (REDD+)Â in Meru Betiri National Park (MBNP) East Java â€“ Indonesia, is considered an essential collaborative program between the Indonesian government, International Tropical Timber Organization (ITTO), and surrounding local communities to mitigate climate change and global warming. In its implementation, community participation plays a significant role because they are impacted directly by REDD+, as stated in the Cancun Agreement and Anchorage Declaration of Indigenous Peoples on Climate Change. Therefore, this research focuses on the participation level and how it contributes to the program. This research used the community participation theory from Choguill and benefited from using mixed methods with a single case strategy. Data were gathered through a questionnaire, a semi-structured interview, and a literature study. The results uncovered that the participation level reached conciliation with the least support of three rungs as a degree of participation. At this stage, the local community and government started to realize their interests by supporting each other. Even so, the government had control in enforcing the decision-making process that involved the community in REDD+. In the end, government and stakeholders at the local and national scales should accelerate community participation through law enforcement and full community involvement in implementing REDD+.